Vysetrení genotypu HCV pomocí kombinace testu Cobas Amplicor HCV 2.0 a reverzní hybridizace Versant HCV Genotype Assay - Nemcová, J; Nemecek, V (Epidemiologie, mikrobiologie, imunologie, 2005)
Genotyping of hepatitis C virus (HCV) is of relevance to scheduling the treatment of patients with chronic hepatitis C (VHC), making their prognosis and monitoring the treatment efficacy. A set of 62 sera testing HCV RNA positive in Cobas Amplicor HCV 2.0 test (CA) were genotyped using Versant HCV Genotype Assay (LiPA) Bayer, i.e. the reverse hybridization method, with the CA amplified product being directly used in the assay. Fifty-six out of 57 samples reactive in reverse hybridization (92%) were genotyped. One sample showed a profile differing from any genotype, five samples were not reactive and one sample was not tested within this study design. Two out of five non-reactive sera and one non-tested serum could be genotyped by nested PCR based reverse hybridization. It can be concluded that the CA product resulting from one-step HCV RNA amplification is suitable for use in genotyping by reverse hybridization. The CA product based genotyping procedure is easier to perform, less time-consuming and less costly. The nested PCR based procedure could be used for typing of sera with lower HCV concentrations nontypeable with the combination of CA and Versant HCV Genotype Assay. Forty-eight selected samples were typed not only by reverse hybridization but also by a serological kit Murex HCV Serotyping 1-6 Assay (Abbot Murex). Thirty-seven (77%) of these sera, including all of three sera negative in reverse hybridization, appeared typeable by this kit. Although less sensitive, serotyping may be of relevance to typing of sera with low HCV levels or not containing detectable viral NA which are nontypeable by reverse hybridization. Thirty-three sera appeared genotypeable by both of the methods tested with the results being in good agreement. In two cases only the serotyping method revealed one more type of virus (mixed genotype) compared to the reverse hybridization.
Keywords: polymerázová řetězová reakce; Polymerase Chain Reaction; Hepatitis C, Chronic; RNA virová; Humans; Nucleic Acid Hybridization; genotyp; RNA, Viral; chronická hepatitida C; Genotype; hybridizace nukleových kyselin; lidé; Hepacivirus